EHealth interventions to support self-management in people with musculoskeletal disorders: a scoping review protocol. Issue 3 (March 2021) - Kelly, Marie; Fullen, Brona; Martin, Denis; McMahon, Sinéad; McVeigh, Joseph G.
ABSTRACT: Objective: The objective of this scoping review is to explore existing literature related to the role of eHealth interventions in supporting self-management in those with musculoskeletal disorders in order to investigate and chart the evidence, and identify any gaps within the literature. Introduction: Musculoskeletal disorders are one of the leading causes of disability worldwide. Self-management interventions are consistently recommended as a core component of treatment for people with musculoskeletal disorders. Given limited health care resources, there is increasing interest in the potential role of eHealth interventions to support self-management in this population. Inclusion criteria: Studies that include adult participants (older than 18 years) with a musculoskeletal disorder will be considered. Studies that include participants with pain of specific pathological origin (eg, infection, malignancy, osteoporosis, inflammatory disease, fracture), those who are pregnant, or individuals following surgery will be excluded. The concept is eHealth interventions that support self-management conducted in any setting and geographical location. All settings and locations will be included. Methods: The following electronic databases will be searched with no limit on publication date: MEDLINE, CINAHL, PsycINFO, Embase, Scopus and the Cochrane Database of Systematic Reviews. A structured search of the gray literature will also be conducted. Studies will be limited to those published in English. Two reviewers will undertake title and abstract screening, followed by full-text screening. Data extraction will be conducted utilizing a standardized form for included studies, and a narrative summary will accompany the charted results and will describe how the results relate to the review's objective. Systematic review registration: Open Science Framework (https://osf.io/29rd6 )